P0363ANTIPROLIFERATIVE AGENTS IN ADDITION TO STEROIDS IN IGA NEPHROPATHY: A SINGLE-CENTER COHORT STUDY. (6th June 2020) - Fontana, Francesco; Vicari, Emanuela; Ligabue, Giulia; Giovanella, Silvia; Alfano, Gaetano; Leonelli, Marco; Cappelli, Gianni
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide. The optimal approach to its treatment remains a significant challenge; despite recent evidence suggesting that immunosuppressive (IS) therapy does not offer significant benefits over supportive treatment alone, many nephrologists continue to offer steroids and other IS drugs to patients in order to reduce proteinuria and prevent progressive kidney dysfunction. Anti-proliferative agents have been used in combination with steroids to treat IgAN, but data regarding their efficacy are controversial, especially in Caucasian patients. Method: We conducted an observational, single center retrospective cohort study to compare the efficacy of different IS regimens in the treatment of IgAN. We included 48 patients (98% Caucasians) with a histological diagnosis of IgAN and without crescentic glomerulonephritis. Patients were divided into three groups according to treatment: steroids alone (ster, n=11), steroids + mycophenolate mophetil (ster+MMF, n=28) and steroids + azathioprine (ster+aza, n=9). Data regarding histological characteristics at diagnosis (MEST-C score, percentage of interstitial fibrosis/tubular atrophy), serum creatinine and proteinuria/creatininuria (P/C) during follow-up, and progression to end stage kidney disease (ESKD) were collected for all patients; adverse events were registered. As primary outcome we considered the complete response at 24 months, defined as a composite outcome of proteinuria/creatininuria < 0.3 and <20% reduction of eGFR during follow-up. Secondary outcomes were: differences in time-averaged proteinuria (TAP), 50% reduction of P/C from baseline, eGFR<30 ml/min, development of ESKD. Results: Mean follow-up for our cohort was 53.88 months. Clinical baseline characteristics did not differ significantly among groups, apart for male sex, more expressed in the steroid group (see table 1). Groups were comparable for histological characteristics at diagnosis (table 2). Interestingly, the addition of anti-proliferative agents did not lead to a reduction of total steroid dose (table 3). Time to complete response in the first 24 months, estimated with Kaplan-Meier method with log-rank test, was not different between the three groups (p=0.44, see figure 1 ). Moreover, we encountered no differences in TAP measured at 6-months periods for the first two years (figure 2 ). Groups were also comparable in time to 50% reduction in P/C from baseline, time to eGFR<30 ml/min, time to ESKD (figure 3 ). No significant adverse events were registered, apart from a higher incidence of diarrhea in the ster+MMF (14%) and ster+aza (11%) groups compared to the ster group. At multivariate logistic regression after adjusting for age and sex, only P/C at baseline was predictive of the absence of complete response (figure 4). Conclusion: In our study, the combination of MMF or aza plus steroid treatment did not offer any benefit over steroids alone in terms of reduction of proteinuria and reduction of eGFR in IgAN patients. Even if safe in terms of severe complications (only mild to moderate diarrhea was reported in the anti-proliferative groups), currently evidence is lacking to support their use in Caucasian patients. Limitations of our study include its retrospective and single-center design, and the relatively low number of patients.